Concerning some words preserved in the dialects that exist in the ancient Turkic written monuments - Chinikulov Nurmurot Djumamurotovich (International Journal on Orange Technologies, 2020)
This paper investigates major points of the concerning some words preserved in the dialects that exist in the ancient Turkic written monuments. On this case, research has been pinpointed both from theoretical and methodological views. Outcomes and shortcomings of the some words preserved in the dialects that exist in the ancient Turkic written monuments.